Private Disclosure and Corporate Value Creation - Yanti Puji Astutie; Anis Chariri; Siti Mutmainah (The Indonesian Journal of Accounting Research, 2019)
The major aim of this paper is to investigate the content of disclosure using crucial case study. Private disclosure has content structure and it is useful in processing value creation. By doing private disclosure, the information of intellectual capital gets perceived by market participants. Disclosure Transformation Theory (Alberti‐Alhtaybat, Hutaibat, & Al‐Htaybat, 2012)was tested through the observation and analysis of the private disclosure functions. This study also expands the view of how the narrative of the corporate value creation is structured and how the corporate knowledge becomes an important part of the dynamic response of the disclosure that changed over time. This study observes new findings regarding intellectual capital disclosure as well as disclosure content in PT. Bank Negara Indonesia Tbk (BNI). BNI has disclosed information value creationin three processes; hierarchy, horizontal, and network by organizing private disclosure media in order to respond on user information needs. This agenda uses analysts as information mediators.Other findings are that private disclosure is a source of information that createsinformation toward a market context of participants to interpret the information in a more appropriate way, the information in private disclosure has superior knowledge in the initial formulation, and incontrolling the portfolio risk of assets allocation to the analyst. Private disclosure has important implications for regulatory policies regarding insider information, corporate disclosure, and corporate governance in financial institutions.